Study Of Pattern of Contraceptive Use Among Young Sexually Active Women Residing in A Slum of Bhopal - Shweta Shrivastava; Preshant Shrivastava; Anshuman Sharma (Medsci Publications, 2016)
Introduction: Much of the sufferings and deaths related to pregnancy or childbirth could be prevented through effective modern contraceptives. This study was conducted to determine knowledge, use of contraceptives and to examine the influences of socio demographic factors on them. Objectives: Objectives of this study was to find out the awareness and use of various contraceptive methods among sexually active women. Material and Method: it was a cross sectionalstudy done in a slum of Bhopal for a period of 3 months from May 2014- July 2014 in242 women of 15-35 yrs age group. Structured performa was used to interview them. Result: Out of 242 women156 (64.5%) were using any method of contraceptive.Majority of them were ie. 203(96%) were aware about sterilization but the most commontype of contraceptive used was condom in 29% cases. Family pressure was the main reasonfor not using any contraceptive method. Conclusion: Majority of them was aware but few are using any kind of contraceptivesmethods. So, there is wide gap in the awareness and usage of contraceptive. So, vigorous,effective and meticulous means of promoting contraceptive use need to be promoted.